The multidrug-resistant Pseudomonas fluorescens strain: a hidden threat in boar semen preservation - Xiong, Zhixuan; Hong, Ziqiang; Li, Xinxin; Gao, Dongyang; Wang, Linkang; Liu, Shudan; Zhao, Junna; Li, Xiangmin; Qian, Ping (Frontiers in Microbiology, 2023)
Although the bacterial composition of boar ejaculate has been extensively studied, the bacterial composition of extended boar semen is often overlooked, despite the potential risks these microorganisms may pose to the long-term preservation of extended boar semen at 15–17°C. In this study, we characterized the bacterial community composition of extended semen and discovered that Pseudomonas spp. was the dominant flora. The dominant strains were further isolated and identified as a potential new species in the Pseudomonas fluorescens group and named GXZC strain, which had adverse effects on sperm quality and was better adapted to growth at 17°C. Antimicrobial susceptibility testing showed that the GXZC strain was resistant to all commonly used veterinary antibiotics. Whole-genome sequencing (WGS) and genome annotation revealed the large genetic structure and function [7,253,751 base pairs and 6,790 coding sequences (CDSs)]. Comparative genomic analysis with the closest type strains showed that the GXZC strain predicted more diversity of intrinsic and acquired resistance genes to multi-antimicrobial agents. Taken together, our study highlights a problem associated with the long-term storage of extended boar semen caused by a P. fluorescens group strain with unique biological characteristics. It is essential to develop a new antibacterial solution for the long-term preservation of boar semen.